PENGARUH ADVERTENSI DAN LAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN PADA PT ELECTRONIC CITY CABANG BOGOR - Basri, Hasan (Universitas Pakuan, 2016)
ABSTRACTThe objective of this research is to find out the effect of advertisement and after-sale service on customer satisfaction at PT Electronic City Bogor. The research was held from November 2011 to Januari 2012. The population is customer of PT Electronic City Bogor, the reachable population is 130 by random sampling. The conclusions from the study are as follows: 1) There is a positive and significant (Î± = 0.05) effect of advertisement on customer satisfaction with regression equation Å¶ = 72.406 + 0.347 X1; 2) There is a positive and significant (Î± = 0.05) effect after sale service on customer satisfaction with regression equation Å¶ = 67.375 + 0.365 X2; 3) There is a positive and significant (Î± = 0.05) effect of advertisement and after-sale service altogether on customer satisfaction with regression equation Å¶ = 42.871 + 0.283 X1 + 0.303 X2. The implications of the research results are as follows: 1) The higher of advertisement offered, will lead to the higher customer satisfaction; 2) The higher the after sale service offered, will lead to the higher customer satisfaction; 3) The higher of advertisement and after-sale service offered altogether, will lead to the higher customer satisfaction.Keywords: Advertisement, after-sale service, and customer satisfaction.